2020
DOI: 10.3390/jcm9061799
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Energetics and Ca2+-Activated ATPase in Obstructive Hypertrophic Cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common genetic disease of the myocardium associated to mutations in sarcomeric genes, but the link between genotype and phenotype remains poorly understood. Magnetic resonance spectroscopy studies have demonstrated impaired cardiac energetics in patients with HCM, and altered mitochondria were described in biopsies, but little is known about possible perturbations of mitochondrial function and adenosine triphosphate (ATP) production/consumption. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Unsurprisingly, disturbances in mitochondrial or antioxidant proteins have been associated with cardiac hypertrophy. In patients with HCM, mitochondrial complex I has been found to be upregulated with elevated ATP levels and increased antioxidant enzymes [46], suggesting hyperactivity of complex I which was proposed to contribute to elevated ROS levels. ROS can also effect ATP levels as evidenced by a study which compared differential status of energy metabolism between myocardial infarction and pathological hypertrophy, where ATP levels were found to be significantly impaired in the former, while being preserved in the latter [47].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Unsurprisingly, disturbances in mitochondrial or antioxidant proteins have been associated with cardiac hypertrophy. In patients with HCM, mitochondrial complex I has been found to be upregulated with elevated ATP levels and increased antioxidant enzymes [46], suggesting hyperactivity of complex I which was proposed to contribute to elevated ROS levels. ROS can also effect ATP levels as evidenced by a study which compared differential status of energy metabolism between myocardial infarction and pathological hypertrophy, where ATP levels were found to be significantly impaired in the former, while being preserved in the latter [47].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“… 25 A previous study reported that in obstructive HCM, ATP2A2/ZTP2A1 played a key role. 30 From completely asymptomatic to outflow tract obstruction, diastolic dysfunction, progressive heart failure, various tachyarrhythmias and sudden cardiac death, the abnormal individualization of clinical phenotype of HCM patients leads to difficulties in clinical decision-making and prognosis evaluation. In addition to significant genetic heterogeneity, the heterogeneity of clinical phenotype is also obvious among different HCMs, and the complex genotype-clinical phenotype relationship also brings challenges to the clinical diagnosis and genetic susceptibility assessment of HCM.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ROS levels can cause oxidative damage to mitochondria and DNA, harm proteins and lipids, activate the mitochondrial permeability transition pore, cause mitochondrial dysfunction, and lead to cellular death. Additionally, it can disrupt the ATP and ADP balance [13,29,70]. While the exact mechanisms of HCM are still not fully understood, previous noninvasive studies have shed light on certain aspects of the disease.…”
Section: Mitochondrial Redox Signalingmentioning
confidence: 99%